Wealth inequality and financial development: Revisiting the symmetry breaking mechanism - ZHANG, Haiping (Institutional Knowledge at Singapore Management University, 2017)
Matsuyama (Econometrica 72(3):853–884, 2004) shows that financial integration may lead to income polarization among inherently identical countries, if these countries are financially underdeveloped, a result he calls “symmetry breaking.” By introducing the minimum investment requirement and within-country wealth inequality into Matsuyama’s framework, I show that wealth inequality is as important as financial development in determining the possibility of symmetry breaking. I then address three practical issues in this model, e.g., the conditions of financial integration, the domestic financial crisis and capital controls, and the world interest rate changes and income volatility.